Vertical greenery as public art: the public’s perspectives - Mansor, Mazlina; Zakariya, Khalilah; Harun, Nor Zalina; Abu Bakar, Nur Izzah (2015)
VG is greenery where plants can be grown on, up, or against internal or external walls of buildings or as freestanding structures. PA is a structure or form that contains an artistic expression. It is placed in a freely accessible public space for people to view. VG has gained tremendous popularity in recent years, and this offers an opportunity to integrate it as a part of public art in cities. A place with a combination of art and aesthetics with environmental principles would become a new urban art that will help extend VG’s survivability and human security in the future. Most research in VG focuses on an environmental and technical aspect that consider its benefits, technical issues, feasibility, acoustic impact, sustainability, system and maintenance. On the other hand, creative methods to approach VG are seldom research upon especially in Malaysia. Hence, this study explores this possibility from the public’s perspectives. The objectives were to identify public’s familiarity and values of VG as PA, and VG attributes to be as a PA. An online survey was used to obtain public’s perspectives on the integration of VG as PA. The target respondents were the public, whereby the link to the survey was sent out to 400 potential respondents. The survey managed to obtain 117 responses, and they were gathered automatically in an Excel spreadsheet. The data were converted into the themes to generate results. Findings yield positive outcomes in terms of the public’s familiarity of the terminologies (i.e. VG and PA), people’s awareness of VG in an urban environment, and the possibilities and potentials of VG to become a PA in Malaysian cities. It means that VG has extended beyond the environmental benefits to include as an art form of people in a city. It will ensure its survivability in the future, not merely as being a trend that will fade away.